Pengaruh Nilai Transaksi Bisnis E-Commerce Dan Jumlah Pengguna Internet Terhadap Pertumbuhan Ekonomi Di Indonesia (Studi Kasus Tahun 2012-2022) - Yuni Sari Simangunsong; Noni Rozaini (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study aims to analyze how and how much influence the variables of the Transaction of E- Commerce and Amount of Internet User have on the Economic Growth spesificly in Indonesia in 2012 - 2022. The analytical method in this study uses multiple linear regression analysis with the Ordinary Least Square method ( OLS) which uses cross-sectional data from districts/cities in Indonesia with the help of Eviews software. The results of this study indicate that Transaction Of E-Commerce variable has a positive effect on the Economic Growth in IndonesiaÂ  and the Amount of Internet User has a positive effect on the Economic Growth in Indonesia.